THE INFLUENCE OF GENDER ON THE STUDENTS’ SCIENCE LEARNING OUTCOMES - Yesny Rosita Oktaviani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research was a comparative quantitative research which aimed to investigate the influence of gender on the students’ science learning outcomes at grade V SDN Kebandaran Pemalang. The subjects in this research were 30 students at grade V SDN Kebandaran Pemalang; there were 15 male students and 15 female students as the research samples in this class. These samples were chosen by using nonprobability sampling or saturated sampling. The method of this research was descriptive statistic with a comparative research design. The data were collected through interviews and documentations. Then, the data were analyzed by operating descriptive statistics and t-test with the prerequisite test, namely normality and homogeneity test. The results of t-test resulted in the value of tcount for 2,236 and ttable for 2,05 with dk=28 and a significance level of 5%. Since the value of t-test was higher than ttable (2,236>2,05), it was concluded that H0 was rejected and Ha was accepted. Based on these findings, it could be concluded that gender significantly influenced the science learning achievement of the students at grade V SDN Kebandaran Pemalang.